Rethinking Death: A Philosophical and Biomedical Model of Ontological Priority - Carroll, La Shun L. (Philosophy and Realistic Reflection, 2025)
This study introduces a new conceptual model of death that repositions it as an ontologically primary state—one that occurs before and initiates the biological processes traditionally associated with dying. Challenging the conventional linear sequence of life → dying → death, the paper argues that death should not be defined by clinical signs such as cardiac arrest or brain inactivity, but as a metaphysical rupture in systemic coherence. Through an interdisciplinary methodology combining philosophical analysis, metaphysical modeling, medical ethics, and systems theory, the paper presents two core frameworks: the Ontological Priority Thesis, which proposes that metaphysical death precedes biological failure; and the Magnetism of Death Hypothesis, which posits that death can propagate inductively across individuals in collective fatal events, akin to magnetic or neural field effects. The study also explores anomalous cases—such as wood, calloused skin, and blood products—that retain systemic function despite localized biological death. These examples support a model of distributed metaphysical vitality dependent on coherence rather than cellular life. Key implications include the need to reassess clinical death markers, revise ethical protocols for end-of-life care and organ donation, and expand philosophical accounts of personhood and consciousness. By rethinking death as a structural inversion of life, this model opens new pathways for research in medicine, metaphysics, and bioethics.